The Commercial Activity of the East India Company 1600_1668: "Historical Study" - Mjbel, Qatran Abbas (Al-Adab Journal, 2021)
Through the chapters of the research, the researcher reviewed the history of the conflict between colonialism, represented by the English East India Company on the one hand, and the Mughal Islamic State in India and its secretions on the other hand, and through our review of the long events, conclusions can be drawn as follows: India was famous around the world as a country that had huge wealth and enormous treasures and produced goods needed by Europeans, which pushed European ambitions towards those regions and the people of Europe began looking for ways to reach India other than that which was known by land and sea because it was subject to the control of Muslims. For nearly a century, the Portuguese were alone in the global shipping lines leading to India, and then they monopolized the trade of eastern goods that they were importing, but rumors of news of India’s cavalry wealth in Europe encouraged all countries to make adventurous attempts from commercial contact to India and break the monopoly of the Portuguese. The British East India Company had a mission since its inception in addition to its basic tasks in trade, detection and colonialism, and that mission is clear in the royal patent under which the company was established, as it stipulates that a company should not be allowed to enter a war with any Christian prince. The colonial monopolistic firms believed under full influence and without rival in the countries in which they had commercial relations, and these firms did not consider Indian trade profitable. The European companies of East India had begun their work at the very beginning of their coming to India with the aim of submitting, subservient and cynical to the Mughal imperial authorities in India, and in this way the British East India Company was able to obtain permission to trade and establish a center for it in Surat on the west coast of the state. Two important things distinguish the European colonial struggle to control India and its bounties during the period of the weakness of the Mughal state and the collapse of its authority in its territories, the first is that the armed colonial conflict between the English and French companies was located in Indian lands while these conflicts between the colonial companies before that period were outside the lands that It was subject to Mughal rule and the second most important matter took place with the money of India and its men, while previous conflicts were at the expense of competing companies financially and humanly. The English East India Company was developing itself to keep pace with its march towards further expansion, conquest and colonialism, and its regulations were modified from time to time under the supervision of the English Parliament. On the Indian side, almost everything was heading to stagnation and decay, as the Mughal state eliminated its territories and the Emirates that it left in those regions. The British colonialism in the Indian subcontinent had priorities for expansion, and the British were marching in this direction according to a deliberate plan aiming at full control over the various affairs of India, its Emirates and its entities, with a focus on eliminating the most dangerous and maintaining weakness.